2017
DOI: 10.1007/s00432-017-2504-5
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide in combination with bendamustine and prednisolone in relapsed/refractory multiple myeloma: results of a phase 2 clinical trial (OSHO-#077)

Abstract: Between July 2011 and September 2013, 25 patients were included in this analysis. The median number of previous treatments was 1 (range 1-2). Twenty-two patients (88%) responded after at least two cycles of RBP (one sCR, five nCR, eight VGPR and eight PR). The median time to first haematological response was 28 days, and median time to best response was 56 days. Due to increased haematological toxicity a dose reduction in most patients required in subsequent cycles of therapy. The median progression-free and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This forest plot illustrates the percentage of events per 100 patient‐cycles for respective therapies. BPR indicates bendamustine, prednisone, and lenalidomide; CPR, cyclophosphamide, prednisone, and lenalidomide; HDACi, histone deacetylase inhibitor; MoAB, monoclonal antibody; MPR, melphalan, prednisone, and lenalidomide; mTORi, mammalian target of rapamycin inhibitor; PI, proteasome inhibitor; R, lenalidomide; Rd, lenalidomide and low‐dose dexamethasone …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This forest plot illustrates the percentage of events per 100 patient‐cycles for respective therapies. BPR indicates bendamustine, prednisone, and lenalidomide; CPR, cyclophosphamide, prednisone, and lenalidomide; HDACi, histone deacetylase inhibitor; MoAB, monoclonal antibody; MPR, melphalan, prednisone, and lenalidomide; mTORi, mammalian target of rapamycin inhibitor; PI, proteasome inhibitor; R, lenalidomide; Rd, lenalidomide and low‐dose dexamethasone …”
Section: Resultsmentioning
confidence: 99%
“…In total, 245 duplicate records were removed, and 1127 records were screened. Ultimately, 51 clinical trials with 61 Len‐containing treatment arms and 9069 patients were included for the analysis based on a priori selection criteria (Fig. ) …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies mainly used bendamustine in combination with other drugs (glucocorticoids, PIs, or IMiDs) as an alternative for patients with RRMM [ 128 ]. The triplet of bendamustine, ixazomib, and DEX (BID) was used in a phase I/II trial in patients with RRMM who previously had received a median of 4 (range 4–9) lines of therapy.…”
Section: Alkylating Agentsmentioning
confidence: 99%
“…However, they achieved a higher degree of both metastasis and tumor growth inhibition when dihydroartemisinin and cyclophosphamide were used in combination [ 54 ]. Liu and colleagues found that a combination of artesunate with lenalinomide, commonly used for the treatment of Multiple Myeloma [ 55 ], produced an impressive enhancement of antineoplastic activity in polyploid cell lines [ 56 ]. Tilaoui and colleagues also observed a synergistic effect when they used vincristine and artemisinin in combination against murin mastocytoma (P815) cells [ 37 ].…”
Section: Artemisinin As a Treatment For Cancermentioning
confidence: 99%